1980
DOI: 10.1111/j.1751-0813.1980.tb05675.x
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation of Salmonella From Jejunal and Caecal Lymph Nodes of Slaughtered Animals

Abstract: One jejunal and one caecal lymph node were sampled from each of 50 cows, 40 yearling cattle, 25 sheep, 20 lambs and 45 pigs after slaughter. Salmonella, Clostridium perfringens and Staphylococcus aureus, all organisms which cause food poisoning in man, were sought by direct plating methods. The samples were also enriched and cultured for Salmonella. Organisms were cultured from 208 (58%) of the 360 lymph nodes; aerobic plate counts yielded up to 25,000 organisms per gram of tissue, although from most infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
2
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 5 publications
0
16
2
1
Order By: Relevance
“…As a result, Salmonella serotypes can on average be isolated from Ͼ10% of apparently healthy animals prior to slaughter (7,27,37). Intestinal carriage or chronic infection of mesenteric lymph nodes may result in contamination of equipment surfaces or workers' hands at processing plants, leading to contamination of carcasses and processed foods (14,29,31,32). These considerations indicate the prime importance of intestinal carriage of Salmonella serotypes in healthy livestock and domestic fowl for food safety in the United States.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, Salmonella serotypes can on average be isolated from Ͼ10% of apparently healthy animals prior to slaughter (7,27,37). Intestinal carriage or chronic infection of mesenteric lymph nodes may result in contamination of equipment surfaces or workers' hands at processing plants, leading to contamination of carcasses and processed foods (14,29,31,32). These considerations indicate the prime importance of intestinal carriage of Salmonella serotypes in healthy livestock and domestic fowl for food safety in the United States.…”
mentioning
confidence: 99%
“…In the United States, between 1 and 6% of farm animals test positive for intestinal carriage of Salmonella serotypes (6-11, 27, 37). Stress during transport and long periods with intermittent feeding increase the spread of Salmonella among livestock and domestic fowl prior to slaughter (5,7,13,18,19,27,29,31,32). As a result, Salmonella serotypes can on average be isolated from Ͼ10% of apparently healthy animals prior to slaughter (7,27,37).…”
mentioning
confidence: 99%
“…Another post-mortem inspection-related concern is the fact that, in modern times, the main meat-related public health risks relate to foodborne pathogens, such as Escherichia coli O157, Salmonella, Campylobacter, that can be shed by healthy animals and contaminate related carcasses/meat, but which are not detectable by traditional, organoleptic meat inspection (Moo et al, 1980;Berends et al, 1993;Edwards et al, 1997, Sorensen andPetersen, 1999). It is likely that the incidence of meat contamination with such non-detectable pathogens is much higher than the reported incidence of conditions/lesions with zoonotic potential identified at slaughter.…”
Section: To What Extent Do Current Inspection Procedures Provide Safementioning
confidence: 99%
“…palpation and incision of organs and lymph nodes, actually can mediate microbial cross contamination between different tissues/organs of the same animal, as well as between different slaughtered animals, resulting in increased public health risks (Samuel et al, 1979;Moo et al, 1980;Blackmore, 1983;McMahon et al, 1987;Sorensen and Petersen, 1999; Opinion SCVPH on fattening pigs, February 2000, Opinion SCVPH on Veal Calves, May 2003). Obviously, from that perspective, palpation and/or incision are undesirable and their omission would be beneficial for public health, as long as such omission did not result in an unacceptable increase in un-detected conditions/lesions of zoonotic potential.…”
Section: To What Extent Do Current Inspection Procedures Provide Safementioning
confidence: 99%
“…Clinicians and diagnosticians have long recognized that Salmonella infections may occur when horses are subjected to stresses of pregnancy, changes in diet, transportation, anaesthesia, surgery, and use of broad spectrum antibiotics. [7][8][9][10][11] It has been suggested that these stress-induced infections are a result of prolonged fecal shedding of Salmonella, which may persist for up to 19 days. 7 The purpose of this study was to identify an asymptomatic carrier state of healthy adult horses for Salmonella enteritidis in lymphoid tissue.…”
mentioning
confidence: 99%